2007
DOI: 10.1002/nbm.1161
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of AZD2171 and vandetanib (ZD6474, Zactima) on haemodynamic variables in an SW620 human colon tumour model: an investigation using dynamic contrast‐enhanced MRI and the rapid clearance blood pool contrast agent, P792 (gadomelitol)

Abstract: The effect of two novel therapeutic agents on tumour haemodynamics was investigated using a fast dynamic contrast-enhanced (DCE)-MRI protocol (0.5 s/image) sensitive to signal changes in both the vascular input function and tumour during the administration of the macromolecular rapid clearance blood pool agent (MM-RCBPA), gadomelitol (P792, Vistarem). This enabled simultaneous measurement of the tumour blood flow per unit volume of tissue (F/V(T), mL/s/mL), the fractional plasma volume (V(p), %), and the perme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 43 publications
7
48
0
Order By: Relevance
“…Anti-angiogenic agents such as anti-VEGF antibody and tyrosine kinase inhibitor were reported that decrease both K trans and IAUGC (O'Connor et al, 2007;Bradley et al, 2008;Bradley et al, 2009), and the decrease in K trans in solid tumours is concerned with the anti-tumour effect (Morgan et al, 2003;Marzola et al, 2004;Nakamura et al, 2006;Flaherty et al, 2008). In this study, K trans , IAUGC 60 , and v p were increased significantly 24 h after the A-83-01 treatment.…”
Section: Discussionmentioning
confidence: 57%
“…Anti-angiogenic agents such as anti-VEGF antibody and tyrosine kinase inhibitor were reported that decrease both K trans and IAUGC (O'Connor et al, 2007;Bradley et al, 2008;Bradley et al, 2009), and the decrease in K trans in solid tumours is concerned with the anti-tumour effect (Morgan et al, 2003;Marzola et al, 2004;Nakamura et al, 2006;Flaherty et al, 2008). In this study, K trans , IAUGC 60 , and v p were increased significantly 24 h after the A-83-01 treatment.…”
Section: Discussionmentioning
confidence: 57%
“…The dynamic signal changes in tissue contrast are proportional to the concentration of the contrast agent in the tissue and related to the functionality of the tumor vessels including permeability, capillary surface area, extravascular extracellular volume, and vascular transfer constant (49)(50)(51). Several studies have shown the use of these methods for preclinical (22,23,52) and clinical (53-56) evaluation of cancer therapies with an antivascular mechanism of action. In this study, it isn't the mechanism of drug efficacy that we are exploring but the impact of vascular function in tumor on pharmacokinetics, pharmacodynamics, and efficacy in two different cancer models.…”
Section: Discussionmentioning
confidence: 99%
“…However, meaningful correlation with response is difficult to achieve, as treatment with chemotherapy and angiogenic inhibitors can often themselves manipulate the expression of these proangiogenic factors. More recently, dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) has been implemented as a noninvasive means to acquire images of tumor blood perfusion and predict response of tumors to therapeutic treatments (20)(21)(22)(23)(24). To complement the functional MRI readout, micro-computed tomographic (microCT) imaging of vascular casts can provide a high-resolution, threedimensional (3D) view of the tumor vessel architecture (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…These include the inhibition of vascular endothelial growth factor-A (VEGF) signaling (1) (a key regulator of tumor angiogenesis, vascular permeability, and neovascular survival), use of vascular disrupting agents (VDAs) such as the tubulin-depolymerising agent combretastatin A-4 (2), or examination of low-dose cytotoxic chemotherapy (3). To monitor the effect of VEGF-signaling inhibitors or VDAs, MRI and CT scans, and in particular dynamic contrast-enhanced MRI and CT, have been used successfully to provide evidence of an effect on tumor blood flow, blood volume, and permeability (4,5). However, an obvious current limitation to being able to understand the full activity of approaches that target the tumor vasculature is the lack of a noninvasive imaging method to quantify changes in tumor vascularity in patients with cancer (6).…”
mentioning
confidence: 99%